IMPACT OF SOCIO-DEMOGRAPHIC CHARACTERISTICS ON TRAVEL EXPENDITURES OF HUNGARIAN TOURISTS IN THE VILLAGE OF SKORENOVAC - Krejić, Živana; Čerović, Slobodan; Milićević, Snežana (Economics of Agriculture, 2016)
Development of rural tourism in Vojvodina affects the survival of village and livelihoods of its people. Despite the numerous problems that villages of Vojvodina face, an example of good practice is the village of Skorenovac in the municipality of Kovin in Banat. Local culture, traditions and legends of the distant past, and a unique way of life of the population of this village are the primary motives and grounds of the arrival of tourists and they affect the development of rural tourism. The aim of this study was to determine whether there are differences in the consumption of Hungarian tourists in the village Skorenovac in relation to age, level of education and gender. The results of research should serve as encouragement of rural households to monitor socio-demographic characteristics of tourists to suitably form the tourist offer in order to increase proft.